Most Significant Changes Experienced by Organic Agriculture Production Training Beneficiaries in Ifugao, Philippines - Marah Joy (Universidade Estadual de Alagoas, 2024)
The Most Significant Change (MSC) technique was used to explore the impacts of the Organic Agriculture Production (OAP) Training Program of Ifugao State University in Ifugao, Philippines. Beneficiaries were asked about changes that resulted from their participation in the program. Themes were identified from these changes. Bennett's hierarchy of program outcomes served as basis in determining levels to which collected changes correspond. There were 105 stories in total. These referred to changes economically, socially as well as changes in beneficiaries' knowledge, attitudes, and skills. Results revealed that the OAP Training Program brought about changes at higher levels that were in line with Bennett's hierarchy. The OAP Training Program brought impacts to beneficiaries economic and social circumstances as well as knowledge, attitudes, and skills.